Report of the committee appointed at a meeting of the commissioners of police, and other inhabitants of the city of Edinburgh, held on the 8th December 1812 (Printed by Lawrie, 1813)
Society for the suppression of beggars. With: Report upon a loan-fund and savings-bank. With a letter from James Bridges to J.H. Forbes.